أي أثر للتطور التكنولوجي والاتصالي في كتب تدريس اللغة العربية ووسائل تعليمها في ماليزيا؟ - Chik, Abdul Rahman (2015)
A critical study on the influence of ICT in the writing of Arabic textbooks and teaching and learning aids.